Celebrity culture and the entertainment industry in Asia : use of celebrity and its influence on society, culture and communication /: use of celebrity and its influence on society, culture and communication. (2017) - Leung, Vivienne; Cheng, Kimmy; Tse, Thomas Kwan-choi
No abstract available